2004
DOI: 10.1203/01.pdr.0000127722.55965.b3
|View full text |Cite
|
Sign up to set email alerts
|

l-Lysine Decreases Nitric Oxide Production and Increases Vascular Resistance in Lungs Isolated from Lipopolysaccharide-Treated Neonatal Pigs

Abstract: Nitric oxide (NO) production may depend on the uptake of L-arginine (L-arg), the substrate for NO synthase in inflammatory lung diseases. The cellular transport of L-arg occurs via the cationic amino acid transporters (CAT), and L-lysine (L-lys) competitively inhibits CAT. Neonatal pigs were treated with lipopolysaccharide (LPS) or vehicle for 4 h. LPS increased exhaled NO (exNO; 0.026 Ϯ 0.003 to 0.046 Ϯ 0.003 nmol · kg Ϫ1 · minϪ1 ; p Ͻ 0.005) and decreased mean systemic arterial blood pressure (89 Ϯ 4 to 67 Ϯ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…We chose to measure exNO production as a measure of total lung NO production. Although measurement of exNO does not differentiate airway vs. vascular sources of NO, we have previously found that in neonatal pigs the measurement of exNO production is a sensitive, rapidly responding measure of physiologically relevant total lung NO production (12). However, our use of whole lung homogenates limits our interpretation of these findings because of limitations in detecting changes in NO production and/or NOS levels localized to specific anatomic locations, such as lung epithelial cells and/or pulmonary vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure exNO production as a measure of total lung NO production. Although measurement of exNO does not differentiate airway vs. vascular sources of NO, we have previously found that in neonatal pigs the measurement of exNO production is a sensitive, rapidly responding measure of physiologically relevant total lung NO production (12). However, our use of whole lung homogenates limits our interpretation of these findings because of limitations in detecting changes in NO production and/or NOS levels localized to specific anatomic locations, such as lung epithelial cells and/or pulmonary vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies show that NO production can be increased by application of exogenous L-arginine, a phenomenon termed "the arginine paradox" (Arnal et al 1995;Wu and Meininger 2000). This effect can be attenuated by pretreatment with L-lysine (Tugba Durlu and Brading 2005) and L-lysine has also been shown to reduce NO production in isolated lung tissue (Carter et al 2004). An explanation may be a compartmentalization of NOS and its substrate, where the L-arginine pool is unavailable to the enzyme unless actively transported there.…”
Section: Discussionmentioning
confidence: 99%
“…In the isolated, perfused lung, exNO was measured as previously described (3,30). Briefly, 25 min after the equilibration of the system, the baseline exhaled gas was collected for 5 min into a mylar balloon attached to the ventilator exhaust port.…”
Section: Methodsmentioning
confidence: 99%